MicroRNAs as regulators, biomarkers and therapeutic targets in liver diseases - Wang, Xiaolin; He, Yong; Mackowiak, Bryan; Gao, Bin (Gut, 2021)
MicroRNAs (miRNAs) are small, non-coding RNAs that post-transcriptionally regulate gene expression by binding to specific mRNA targets and promoting their degradation and/or translational inhibition. miRNAs regulate both physiological and pathological liver functions. Altered expression of miRNAs is associated with liver metabolism dysregulation, liver injury, liver fibrosis and tumour development, making miRNAs attractive therapeutic strategies for the diagnosis and treatment of liver diseases. Here, we review recent advances regarding the regulation and function of miRNAs in liver diseases with a major focus on miRNAs that are specifically expressed or enriched in hepatocytes (miR-122, miR-194/192), neutrophils (miR-223), hepatic stellate cells (miR-29), immune cells (miR-155) and in circulation (miR-21). The functions and target genes of these miRNAs are emphasised in alcohol-associated liver disease, non-alcoholic fatty liver disease, drug-induced liver injury, viral hepatitis and hepatocellular carcinoma, as well liver fibrosis and liver failure. We touch on the roles of miRNAs in intercellular communication between hepatocytes and other types of cells via extracellular vesicles in the pathogenesis of liver diseases. We provide perspective on the application of miRNAs as biomarkers for early diagnosis, prognosis and assessment of liver diseases and discuss the challenges in miRNA-based therapy for liver diseases. Further investigation of miRNAs in the liver will help us better understand the pathogeneses of liver diseases and may identify biomarkers and therapeutic targets for liver diseases in the future.